Preparation of hydrogel from bee pollen extracts / Nurfaizah Mohamed - Mohamed, Nurfaizah (2023)
Hydrogels are water-expanding insoluble polymers that are available as sheet, amorphous gel, and sheet hydrogel-impregnated dressings. Chitosan/PVA hydrogel layers are used to make a hydrogel that contains stingless bee pollen extract and could be used as wound dressing materials. The main purpose of this study is to prepare the hydrogel wound dressing with containing bee pollen extracts at different concentrations which at 5ml, 10ml and 15ml. Their tensile strength, gel fraction and porosity were investigated. In this study, hydrogel incorporated with different concentration of 5, 10,15 ml stingless bee pollen extract was obtained successfully. Sample 1 which is hydrogel with 5ml of bee pollen extract has a higher tensile strength with value of 0.348 N.mm2 and higher gel fraction which the value is 25%.